Astrocytes and Alexander disease: the first - but not last - primary astrocyte disease - Messing, Albee (Henry Stewart Talks, 2011)
GFAP in astrocytes: isolation, genetics and function, Alexander disease: clinical and pathologic features, Mouse models for studying pathogenesis, Potential therapeutic approaches: reduction of GFAP and manipulation of stress response, Update interview: Genetics of Alexander Disease, Update interview: GFAP-delta isoform, Update interview: New model systems, Update interview: Role of TDP-43, Update interview: Defects in Stem Cells and Adult Neurogenesis, Update interview: Potential Mechanism for Myelin Deficits, Update interview: Antisense Therapeutics
Updated at 2020/09/22